Tax Policies and Economic Growth: A Comparative Review - Mellisyah, Mellisyah (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study examines the impact of various tax policies on economic growth through a comparative analysis of different taxation models, including progressive, regressive, and corporate tax structures. It aims to identify best practices in tax policy design that balance revenue generation, investment stimulation, and economic equity while addressing emerging challenges such as digital taxation and environmental tax policies. Research Design and Methodology: The study employs a systematic literature review (SLR) methodology, synthesizing existing empirical and theoretical research from peer-reviewed journals, policy reports, and economic analyses. The review focuses on comparative assessments of taxation policies across developed and developing economies, evaluating their role in fostering fiscal stability and economic expansion. Findings and Discussion: The findings indicate that progressive tax structures contribute to income redistribution but may discourage investment if tax rates are excessively high. In contrast, regressive tax policies ensure stable revenue flows but disproportionately impact low-income groups. Corporate taxation influences foreign direct investment (FDI) and business competitiveness, requiring a balanced approach between fostering economic activity and ensuring adequate government revenue. The study also highlights gaps in digital taxation and environmental tax implementation, emphasizing the need for global cooperation and regulatory alignment to enhance tax efficiency. Implications: The study provides strategic recommendations for policymakers to develop adaptive, data-driven tax policies that promote sustainable economic growth. It underscores the importance of fiscal transparency, digital tax administration, and well-structured tax incentives to enhance compliance and prevent tax evasion. Future research should focus on empirical analyses of taxation's long-term effects on economic development and the role of digital transformation in tax governance.